Pengaruh Penambahan Ekstrak Bunga Telang terhadap Sifat Kimia dan Organoleptik pada Produk Minuman Cendol - Atia Fizriani; Ati Atul Quddus; Hari Hariadi (Program Studi Teknologi Pangan, 2020)
Cendol is a typical beverage product which is much popular among children and adults. A usual colour of cendol is green. Concern for some consumers of the colours found in cendol is a produced by artificial colorant that may have a negative impact for consumen. The butterfly pea (Clitoria ternatea L.). pigmetns, antocyanin, can be used as alternative for natural food coloring. This research aims to determine the influence addition of the butterfly pea extracts to proximate value, antocyanin total, antioxidant activity, and organoleptic test such as the color, flavor, aroma, and texture. The product of cendol was made from various the addition of 0.25 g, 0.50 g, and 0.75 grams flowers extract. The result showed that cendol with addition of 0,75 g flower extract was the higest total antocyanin content (235,24 mg/L) which had moisture content 82,34%, ash content 1,10%, protein 2,16%, fat 4,18%, carbohydrate 11,95%, and the result of organoleptic test were score of color 2,02; taste 1,94; aroma 1,80 and texture 1,94.